IMPACT OF THE SECONDARY EDUCATION DEVELOPMENT PROGRAM ON ACCESS TO SECONDARY EDUCATION IN TANZANIA - Dismas Alex; Fredrick Manang (Yayasan Education and Social Center, 2022)
Limited access to secondary education is a growing challenge especially in many developing countries, where more young individuals of secondary school age are pushed back to join higher level of education beyond primary level because of few number of secondary schools, hence continued to be less competitive in the national labor markets. Evidence suggests that, if investment in school construction interventions is made, more people will be aware about schools and other education services, hence the cost of education will be reduced and education attainments can be attained. The study used Difference in Difference (DID) multiple regression model to evaluate the impact of the secondary education development program (SEDP) on access to secondary education in Tanzania. The study employed secondary data of 2012 Population and Housing Census data from the National Bureau of Statistics (NBS) and secondary schools census data from Presidents Office Regional Administration and Local Government (PO-RALG). The study found that, SEDP has significant impact on the number of secondary schools and student enrolment in secondary schools in Tanzania. The results revealed that, number of secondary schools and students enrollment increases more in wards that have received SEDP, than it would have without SEDP intervention